“I deserve this”: A Phenomenological Study Toward Online Impulse Buying Behavior of Service Contractors - Somera, Kristine (Journal of Interdisciplinary Perspectives, 2024)
With the rising popularity of digital marketplaces, the phenomenon of "impulse buying" online has become increasingly common. This study examined the lived experiences of Filipino service contractors regarding this phenomenon, utilizing the Hedonic Motivation Theory and the Stimulus-Organism-Response framework to explore the driving forces behind their inclination for online impulse buying and their perception of "I deserve this." The researcher used the Impulse Buying Scale developed by Rook and Fisher in 1995 to identify ten service contractors from the province of Aurora who scored high and met the specific criteria. These ten participants were interviewed individually online. The data analysis revealed six categories summarizing the lived experiences of service contractors regarding online impulse buying behavior: a) The emergence of online impulse buying behavior among service contractors, b) The motivations behind service contractors' online impulse buying, c) The positive or therapeutic effects of online impulse buying, d) The negative impacts of online impulse buying, e) The extent to which service contractors engage in online impulse buying, and f) The coping strategies employed by service contractors in response to online impulse buying. This study provides valuable insights for researchers, particularly those in the Philippines, who wish to explore various dimensions of online impulse buying.